Kontribusi Wisata Pantai Tiku Kecamatan Tanjung Mutiara terhadap Perekonomian Masyarakat Lokal - Putra, Afdal Wahyudi; Chandra, Deded (TSAQOFAH, 2025)
This study aims to assess the contribution of Tiku Beach tourism in Tanjung Mutiara Subdistrict to the local economy and to identify the economic challenges faced by small-scale entrepreneurs in the area. A descriptive qualitative approach was employed, with data collected through interviews with business owners, vendors, service providers, tourism workers, and local residents, supported by field observations. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that Tiku Beach tourism significantly contributes to local economic improvement, particularly by creating business opportunities and increasing daily income levels—from an average of Rp50,000–Rp100,000 to Rp200,000–Rp250,000. However, local entrepreneurs face three main challenges: income fluctuations due to seasonality, competition among similar businesses, and predominantly traditional business management practices. The study concludes that Tiku Beach tourism plays a vital role in driving the local economy, but sustaining its contribution requires strategic efforts in capacity building, managerial support, and strengthening the competitiveness of tourism-related enterprises.